2015
DOI: 10.1074/jbc.m114.629170
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Driving Forces Required for Efficient Secretion of Autotransporter Virulence Proteins

Abstract: Background: Many virulence proteins are secreted using the autotransporter system. Results: Autotransporter proteins do not fold until secreted and are secreted poorly in the absence of folding. Conclusion: Folding helps drive autotransporter secretion, but another energy source is required for its initiation. Significance: Our conclusions reconcile apparent contradictions in the literature and importantly contribute to understanding and manipulating autotransporter secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 55 publications
(74 reference statements)
3
32
0
Order By: Relevance
“…This is consistent with the need for an estimated 30–45 residues N-terminal to the β-barrel to form a proposed early intermediate in OM translocation, consisting of an extended loop that crosses the OM twice, connecting the waiting passenger in the periplasm to the cell surface and back to the periplasmic N-terminus of the β-barrel (Fig. 1) (Drobnak et al, 2014; Ohnishi et al, 1994; Pohlner et al, 1987). While the disordered portion of the linker can be crucial for OM translocation, the PL region primarily appears to be necessary for the folding (and potentially secretion) of wild type, β-helical passengers that are also much larger than the commonly used heterologous passengers (such as cholera toxin B subunit).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This is consistent with the need for an estimated 30–45 residues N-terminal to the β-barrel to form a proposed early intermediate in OM translocation, consisting of an extended loop that crosses the OM twice, connecting the waiting passenger in the periplasm to the cell surface and back to the periplasmic N-terminus of the β-barrel (Fig. 1) (Drobnak et al, 2014; Ohnishi et al, 1994; Pohlner et al, 1987). While the disordered portion of the linker can be crucial for OM translocation, the PL region primarily appears to be necessary for the folding (and potentially secretion) of wild type, β-helical passengers that are also much larger than the commonly used heterologous passengers (such as cholera toxin B subunit).…”
Section: Discussionsupporting
confidence: 79%
“…3), and because so few well-characterized stable cores and autochaperones have been identified, the temptation to extend structural and functional significance to a conserved sequence feature must be resisted. Similarly, although C-terminal passenger stability has also been linked to efficient OM secretion (Brockmeyer et al, 2009; Drobnak et al, 2014; Renn et al, 2012; Soprova et al, 2010), and hence it might be tempting to speculate that the PL region plays a key role in the secretion of wild type β-helical passengers. However, a similar effect of C-terminal passenger stability on secretion has also been observed in at least one AT without an identified PL region (Ivie et al, 2010).…”
Section: Common Themes (And Variations) For Characterized Autotranspomentioning
confidence: 99%
“…All of the C‐terminal domains that have been crystallized to date form nearly superimposable 12‐stranded β‐barrels (Oomen et al ., ; Barnard et al ., ; van den Berg, ; Tajima et al ., ; Zhai et al ., ). The two major domains are connected by a short ‘linker’, part of which forms an α‐helical segment that is embedded inside the β‐barrel domain (Drobnak et al ., ,). In a recent survey, hidden Markov models identified > 1500 genes that likely encode autotransporters in the genomes of Proteobacteria, Chlamydiales and Fusobacteria and confirmed that the autotransporter pathway is very widespread (Celik et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…45 The translocation of the autotransporter passenger domain, which represents the mature virulence protein, across the bacterial outer membrane is mediated by its own co-translated C-terminal transmembrane translocator domain and the folding properties of the passenger. 40,41,46 Pertactin is an extracellular integrin binding protein that mediates attachment of B. pertussis to the ciliated cells of the upper respiratory system. 47 The pertactin passenger domain is 539 aa long and has a predicted net charge of −2.4 e at pH 7.5.…”
mentioning
confidence: 99%